INJURY PROFILE IN YOUNG FEMALE ADOLESCENTS - A CASE STUDY FROM ISLAMABAD - Shaikh, Masood Ali; Shaikh, Irshad Ali (Journal of Ayub Medical College Abbottabad, 2004)
Background: Injuries are an under recognized public health problem globally. We assessed the prevalence and correlates of injuries in adolescent school girls. Methods: A cross-sectional survey with convenience sampling was conducted among the two girl’s middle schools in Islamabad, using structured, self-administered, anonymous and pre-tested questionnaire. All the class seven and eight students attending the school on the day of study were distributed questionnaires in the classrooms, who handed-over the completed questionnaires to their designated teacher. Data was analyzed for frequencies and counts with STATA 8. Results: One hundred eighty-two questionnaires were completed; average age of respondents was 12 years (range 11-14). Cumulatively, 78 (42.8%) students reported sustaining 93 medically attended unintentional injuries in the past year; among these 11 (14.1%) reported two injuries and 2 (2.6%) reported three injuries. For 43 (46.2%) injuries, respondents consulted a general practitioner (Doctor practicing near home), while for the rest of injuries, students were taken to the hospital for treatment. Conclusion: Medically attended unintentional injuries in the preceding one year were common in the school girls, with home being the most frequent place of injuries. Falls with injuries on hands and arms was the most common site of injuries. Key Words: Injuries Female Adolescents Students Pakistan